NEW APPROACHES CONCERNING THE DEVELOPMENT OF THE ECOTOURISM IN ROMANIA - Petrică ŞTEFAN; Silviu GHEORGHE; Cristian CUTAŞ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development, 2014)
The hereby study undertakes to introduce the certification procedure in ecological tourism, as well as the criteriathat must be fulfilled by the lodging units that wish to voluntarily adhere to this modern form of tourism. In ourcountry, the Certifying System in the Ecotourism is used by the Romanian Association of Ecotourism (AER) and thisadjusts the international experience to the Romanian context. This has been developed in conformity with theAccreditation Program in Nature and Ecotourism promoted by the Australian Association of Ecotourism (NEAPbeing the first accreditation system in ecological tourism) and in conformity with Nature’s Best of the SwedishAssociation of Ecotourism (the first accreditation system in Ecotourism in the northern hemisphere). A key elementin the certification procedure consists of drawing up a plan of sustained development which should answer theentirety of certification requirements. The hereby study shows a model of sustained development plan that can beused by managers and owners of lodging units that wish to acquire the certification in tourism.